### Discussion :: Applied Mechanics - Section 1 (Q.No.21)

M Zafar said: (Apr 5, 2015) | |

Any one explain how? |

Jay Bermudo said: (May 12, 2015) | |

If you look closely, there are three cables in the problem. It says the word "lift" three times so the cable is three. So gravity divided by three is the answer. |

Amr said: (Jul 19, 2015) | |

According to motion equation sum of forces = mass*acceleration (a). In case going down force up is tension t and down is weight mass*g. So m*g-t = m*a. So t = m*g-m*a....(1). In case of going up force up is 2*t and force down is m*g. So 2*t-m*g = m*a. So from 1 t = m*g-m*a then 2*m*g-2*m*a-m*g = m*a. Then m*g-2*m*a = m*a. So m*g = 3*m*a. So g = 3 a. So a = g/3. |

Kiran said: (May 21, 2017) | |

Yes, your explanation is correct @Amr. |

Suneel Kurmi said: (May 30, 2017) | |

Tension in the cable. Moving downward T= m(g-a). Upward T=m(g+a). B option is correct. |

#### Post your comments here:

Name *:

Email : (optional)

» Your comments will be displayed only after manual approval.